Design and Analysis of Cybersecurity Information Sharing Mechanism Between Computer Security Incident Response Teams (CSIRT) in Indonesia on Blockchain Technology Through Hyperledger Composer and Interplanetary File System (IPFS) - Hariyanto, Fajar; Ramli, Kalamullah (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
Sharing cybersecurity information among the Computer Security Incident Response Team (CSIRT) is a crucial step in enhancing organizational cybersecurity. However, a primary challenge faced is the lack of trust among users regarding the confidentiality, integrity, and availability of shared information. This study proposes a new approach by designing a mechanism for sharing cybersecurity information among CSIRTs in Indonesia on blockchain technology using Hyperledger Composer. This approach offers an innovative solution by leveraging the advantages of blockchain technology. Through this approach, cybersecurity information can be shared in a decentralized manner, overcoming the weaknesses of centralized systems, and enhancing overall information security. Another advantage of blockchain technology is its high performance and scalability, enabling increased speed, and user capacity in the process of sharing information. By implementing a blockchain-based mechanism for sharing cybersecurity information, this research aims to ensure crucial aspects of information security, namely confidentiality, integrity, and availability. The contribution of this study is not only in enhancing organizational cybersecurity but also in providing an innovative solution to practical challenges in sharing cybersecurity information among CSIRTs.